Effect of KOH as Stabilizer on Mechanical and Chemical Properties of Liquid Rubber Compound - Dwi Sutanto1, Teja; Setiaji3, Bambang; Wijaya3, Karna; Eka Suharto2, Totok (Asian Journal of Chemistry, 2014)
The effect of KOH stabilizer on mechanical and chemical properties of liquid rubber compound has been examined. Liquid rubber made by mixing stearic acid and zinc oxide as activator, 3,5-di-tert-butyl-4-hydroxy toluene and liquid smoke as antioxidant, CaCO3 as filler, dibenzothiazole disulfide and tetramethyl thiuram disulfide as accelerator, KOH as stabilizer and sulphur as vulcanizing agent with concentrated latex at room temperature, then maturated for 72 h. In this research the use of KOH stabilizer was varied as 3, 4, 5, 6 and 7 phr. Before being examined, rubber film made from liquid rubber compound by dyeing process then vulcanization done at 100 °C with water vapor. The rubber film which produced from liquid rubber compound then was characterized their mechanical and chemical properties such as resistance to heating, resistance to acid and alkaline resistance. The result showed that KOH content changed the mechanical and chemical properties of liquid rubber compound.